2018
DOI: 10.1002/adfm.201806346
|View full text |Cite
|
Sign up to set email alerts
|

2D Tellurium Based High‐Performance All‐Optical Nonlinear Photonic Devices

Abstract: Tellurium (Te), as one of the rarest stable solid elements far more common in the universe than on earth, is a p‐type semiconductor with excellent optical properties. Herein, a novel two‐dimensional (2D) Te nanosheets (Ns)‐based air‐stable nonlinear photonic devices: all‐optical switcher and photonic diode, owing to its strong light–matter interaction in the visible‐to‐infrared band are reported. The findings validate that the proposed photonic diode can be utilized for the function of nonreciprocal light prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
140
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 188 publications
(141 citation statements)
references
References 61 publications
1
140
0
Order By: Relevance
“…Monoelemental tellurium (Te), located in group VI A in the periodic table, has attracted great interests over the past decade due to its intriguing properties, such as excellent photoresponse, fast photoconductivity, high thermoelectricity, and piezoelectricity . As a non‐layered material, Te has a chiral‐chain crystal structure, and the individual Te atoms are stacked together by van der Waals forces . Like the famous black phosphorus (BP), Te has a layer‐dependent energy bandgap ( E g ) that can be tuned from ≈0.35 to ≈1.0 eV as the thickness of Te decreases from bulk to monolayer .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoelemental tellurium (Te), located in group VI A in the periodic table, has attracted great interests over the past decade due to its intriguing properties, such as excellent photoresponse, fast photoconductivity, high thermoelectricity, and piezoelectricity . As a non‐layered material, Te has a chiral‐chain crystal structure, and the individual Te atoms are stacked together by van der Waals forces . Like the famous black phosphorus (BP), Te has a layer‐dependent energy bandgap ( E g ) that can be tuned from ≈0.35 to ≈1.0 eV as the thickness of Te decreases from bulk to monolayer .…”
Section: Introductionmentioning
confidence: 99%
“…As a non‐layered material, Te has a chiral‐chain crystal structure, and the individual Te atoms are stacked together by van der Waals forces . Like the famous black phosphorus (BP), Te has a layer‐dependent energy bandgap ( E g ) that can be tuned from ≈0.35 to ≈1.0 eV as the thickness of Te decreases from bulk to monolayer . First‐principles density functional theory (DFT) calculations revealed that 2D Te forms a natural stable state with higher carrier mobility ranging from hundreds to thousands of cm 2 V −1 s −1 , comparable to that of molybdenum disulfide (MoS 2 ) .…”
Section: Introductionmentioning
confidence: 99%
“…After that, Te nanostructures based on other substrate such as sapphire, graphene/4H-SiC and HOPG have also be studied in recent years [137][138][139][140][141][142][143]. In general, there are many kinds of synthetic methods, including physical vapor deposition (PVD) [135], MBE [138], LPE [144][145][146], hydrothermal reaction [131,132,147,148], CVD [130] and thermal evaporation deposition [149,150]. Without consideration of the crystal scale, both Lin et al and Wu et al demonstrated free-standing exfoliated Te nanosheets at the size of several hundred nanometers in polarized solvent by ultrasonic bath and centrifugation [144,146].…”
Section: Telluriummentioning
confidence: 99%
“…In general, there are many kinds of synthetic methods, including physical vapor deposition (PVD) [135], MBE [138], LPE [144][145][146], hydrothermal reaction [131,132,147,148], CVD [130] and thermal evaporation deposition [149,150]. Without consideration of the crystal scale, both Lin et al and Wu et al demonstrated free-standing exfoliated Te nanosheets at the size of several hundred nanometers in polarized solvent by ultrasonic bath and centrifugation [144,146]. To date, they found greater air stability and biocompatibility of Te nanosheets after the functionalization of glutathione (GSH), which can be used in the photodynamic therapy agents.…”
Section: Telluriummentioning
confidence: 99%
See 1 more Smart Citation